Industrial concentration - Utton, M. A. (Harmondsworth : Penguin, 1970)
This book contain theories of the penguin modern economics. The book further sets the problems of measurement in a framework of economic analysis, and applies concentration measurement to economic history and policy.
includes references
Bibliography: p. [125]-128.
asm; 14/02/19
Loans
Keywords: Big business; Big business